Online Basic Life Support Course to Increase Knowledge and Skill of Nursing Students - Suwaryo, Putra Agina Widyaswara; Santoso, Dadi; Waladani, Barkah (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This result with paired t-test showed a significant increase in learning [pre-test (6,31.62), post-test (9.20.84), p <0.001). the increase in mean scores after attending online course was significant (p <0.001). there was no difference in learning (p = 0.482) after observation. The simulation results were carried out after course: check response (90.2%), exposed chest (93.1%), checked for pulse (93.1%), checked for breathing (87.2%), called emergency services (72.5%), use a defibrillator (86.2%), correct hand position (82.4%), perform chest compressions (92.4%), perform compressions of at least 2 inch (82.4%), full recoil (89.2%), provide ventilation (94.1%), use AED (84.3%), and positioned the pads (89.2%). BLS course conducted online is an alternative course and effective method to provide knowledge and skills, where students continue to accurately implement BLS actions